Network performance analysis : using the J programming language - Holt, Alan, 1965- (Springer, 2017)
Introduction -- Fundamentals of the J Programming Language -- Programming in J -- Network Calculus -- Stochastic Processes and Statistical Methods -- Traffic Modeling and Simulation -- Chaotic Maps -- ATM Quality of Service -- Congestion Control.